Evaluations of the physical and physicochemical properties and perception of liking of conventional and low-calorie orange jellies - Simoncello, Bruna Aparecida; Department of Food, Federal University of Ouro Preto, Campus Morro do Cruzeiro, Zip code: 35400-000 Ouro Preto, Minas Gerais, Brazil (2020)
There is a growing demand for reduced-calorie products today due to changing dietary habits of the population. This challenges the food industry to design products that resemble conventional ones concerning physical, physicochemical, and sensory characteristics. Thus, the objective of this study was to evaluate the physical and physicochemical properties and perception of the liking of conventional and low-calorie orange jellies. Two different formulations (conventional and low-calorie) of each type of orange jelly were prepared and assessed under physical, physicochemical, sensory, and statistical analysis. The results showed that the formulated jellies presented differences in terms of the physical and physicochemical parameters studied, except for the color parameter a*. Conventional jelly had lower values of pH, acidity, and soluble solids, and higher moisture content. Additionally, conventional jelly was found to be lighter, more yellow, less rigid, and less viscous, than low-calorie orange jellies most likely due to its shorter cooking time. The two sensorial methodologies (time-intensity and temporal dominance of sensations analysis) used showed differences in perception of the evaluated stimuli, with the conventional orange jelly having higher dominance intensities for sweet taste and acidity. The low-calorie orange jelly presented a bitter taste, most likely due to the use of sweeteners.